2020
DOI: 10.1002/saj2.20139
|View full text |Cite
|
Sign up to set email alerts
|

Modified self‐adaptive model for improving the prediction accuracy of soil organic matter by laser‐induced breakdown spectroscopy

Abstract: Soil organic matter (SOM) significantly influences soil fertility, biology, and the global C cycle. Laser‐induced breakdown spectroscopy (LIBS) is attractive, as it can measure SOM accurately and quickly with minimal sample preparation and effective cost. Our earlier self‐adaptive (SA) model based on individual distances between LIBS soil spectra coupled with partial least squares (PLS) was favorable for SOM prediction. To optimize this model by including soil identification via the use of a hybrid distance be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…For example, the soil samples in Study Area 1 were mainly meadow solonchak soil, and the frequency statistics of the selected samples (Figure 7) suggested the samples in Study Area 1 were selected with higher probability for calibration than the unknown samples from the study, even if the SD and CV in Study Area 2 were larger than those in Study Area 1 (Table 1). In terms of larger sample selection for calibration at a national scale, 250 samples from all over the country were used with SAM-PLSR and LIBS for predicting SOM [22]; the results showed R 2 , RPD and RMSE values of 0.89, 2.82 and 5.84 g kg −1 , respectively (Figure 9), which showed lower model performance compared with that in Figure 8. For a national database, the SD and CV of samples were 16.77 and 63.39%, respectively, which were larger than those of the samples in Study Area 1.…”
Section: Influences On Sam-plsr Modeling Performancementioning
confidence: 99%
See 3 more Smart Citations
“…For example, the soil samples in Study Area 1 were mainly meadow solonchak soil, and the frequency statistics of the selected samples (Figure 7) suggested the samples in Study Area 1 were selected with higher probability for calibration than the unknown samples from the study, even if the SD and CV in Study Area 2 were larger than those in Study Area 1 (Table 1). In terms of larger sample selection for calibration at a national scale, 250 samples from all over the country were used with SAM-PLSR and LIBS for predicting SOM [22]; the results showed R 2 , RPD and RMSE values of 0.89, 2.82 and 5.84 g kg −1 , respectively (Figure 9), which showed lower model performance compared with that in Figure 8. For a national database, the SD and CV of samples were 16.77 and 63.39%, respectively, which were larger than those of the samples in Study Area 1.…”
Section: Influences On Sam-plsr Modeling Performancementioning
confidence: 99%
“…Compared with the conventional PLSR method, the values of R 2 and RPD were increased by 1.60 and 1.96 times, respectively, and the RMSE value was reduced by almost 50%. The SAM-PLSR model combined with LIBS spectra was also used for predicting SOM, and the prediction accuracy was significantly improved compared with the conventional PLSR method [22]. Moreover, different spectral similarity calculation methods, such as correlation coefficients (CC), ED, Mahalanobis distance (MD), angle cosine (AC) and k-medoids (KM), have been used on various types of soil samples to determine the soil property prediction performance of the SAM-PLSR algorithm, and the SAM-PLSR based on ED and CC had the optimal model accuracy and robustness in the prediction of SOM; furthermore, a modified SAM-PLSR with LIBS spectra, based on individual distance and hybrid distance, was introduced [22], and the study also showed that the ED-based SAM-PLSR method showed good prediction performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, cell recognition with LIBS remains unreported, and simultaneous classification for four types of cancer cells is a challenge. Although classification models such as SVM, RF, , and SOM achieved excellent performance coupled with LIBS, the algorithm’s inner mechanism was hidden to the user (called the “black box”) and lacked interpretability and extensibility . Consequently, we adopted a deep learning model: a one-dimensional convolution neural network (1D-CNN) with gradient-weighted class activation mapping (Grad-CAM) to build a “transparent” model and provide interpretability of results …”
Section: Introductionmentioning
confidence: 99%